2022
DOI: 10.2355/isijinternational.isijint-2021-238
|View full text |Cite
|
Sign up to set email alerts
|

Cracking Process in Delayed Fracture of High-Strength Steel after Long Atmospheric Exposure

Abstract: This paper is the first microscopic observation of the entire cracking process in delayed fracture of highstrength steel bolt after long-term atmospheric exposure. A sufficiently fresh fracture surface exhibits the initiation of the propagating crack in a thin zone beneath the screw groove, resulting from the merging of multiple cracks nucleated therein. The fracture morphology is initially intergranular, exhibiting the threedimensional shape of prior austenite grains, but the stress and strain states at the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…In the present study, the two crack initiation sites with the low hydrogen content at the level absorbed by atmospheric corrosion are consistent with the previously reported result that the crack initiation sites of the bolts that fractured after 16 years of exposure to the atmosphere originated from multiple sites near the screw grooves 17) . Crack initiation in the case of delayed fracture at a low hydrogen content absorbed in atmospheric conditions is not necessarily consistent with the site of the principal maximum stress and the maximum local hydrogen concentration due to hydrostatic stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the two crack initiation sites with the low hydrogen content at the level absorbed by atmospheric corrosion are consistent with the previously reported result that the crack initiation sites of the bolts that fractured after 16 years of exposure to the atmosphere originated from multiple sites near the screw grooves 17) . Crack initiation in the case of delayed fracture at a low hydrogen content absorbed in atmospheric conditions is not necessarily consistent with the site of the principal maximum stress and the maximum local hydrogen concentration due to hydrostatic stress.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple cracks probably propagated together in a step-like manner on the fracture surface. 17) It has been reported that the maximum diffusible hydrogen content absorbed in tempered martensitic steel through atmospheric corrosion under applied stress was approximately 0.2 mass ppm (referred to here as simply ppm). 18) Therefore, crack initiation and subsequent propagation under low hydrogen content levels 1), 18) absorbed by atmospheric corrosion may not be sufficiently explained by crack initiation from a single site, as reported for conventional stress-or strain-controlled types.…”
Section: Introductionmentioning
confidence: 99%
“…Where ρ is the density of the specimen; c is the specific heat of the sample; η is heat transfer efficiency, determined by Eq. (2). By substituting the data obtained from the thermal simulation experiment into Eqs.…”
Section: Experiments Results and Correctionmentioning
confidence: 99%
“…Sheng-De HU, 1,2) Lin ZHU, 1) * Mao ZHANG, 2) Xin-Yun WANG 2) and Sheng LIU 1) the understanding of material damage and fracture behavior.…”
Section: Modeling and Evaluation Of Damages In Bismuth-containing Sta...mentioning
confidence: 99%
See 1 more Smart Citation